Aplikasi Pemesanan Jasa Laundry Berbasis Android - Muhammad Reza Khalafi; Ester Lumba (UNIVERSITAS KALBIS, 2022)
The purpose of this research is to produce an application to search and order from the nearest laundry based on Android. Android-based laundry service ordering application provides an alternative to finding the nearest laundry. Laundry search using an internet connection and connected to the Global Positioning System (GPS), for laundry owners can register their business first and for users will able to find the nearest laundry place by comparing the distance between users and laundry places that have been previously registered. The development method used in this research is the Rational Unified Process (RUP) with the Unified Modelling Language (UML) system modelling. This application was built using Android Studio software with Java programming language, XML, MySQL as a database and PHP as a database management. The results of this study are Android-based laundry service ordering applications.